Pengaruh Dukungan Teman Sebaya pada Kesejahteraan Psikologis Mahasiswa Mengerjakan Skripsi di Bukittinggi - Melan Safitri; Devi Rusli (Jurnal Family Education, 2023)
his study aims to find out the Influence of Peer Support on Psychological Well-Being in the Senior Students are Working on Their Thesis in Bukittinggi. The research design is used quantitative. This study useses a Likert scale. The scale used is the subjective well-being and peer support scale. The subjects in this study are 130 senior students are working on their thesis. Sampling uses insidental sampling technique. Based on the results with the calculation of regression test, the value of F is 26,503 with a significance of 0.000 (p<0.05) is obtained. These results indicate that there is significant influence in Peer Support on Psychological Well-Being in the Senior Students are Working on Their Thesis in Bukittinggi